Relationship between duration and extent of oedema and visual acuity outcome with ranibizumab in diabetic macular oedema: A post hoc analysis of Protocol I data - Sadda, Srinivas R.; Campbell, Joanna; Dugel, Pravin U.; Holekamp, Nancy M.; Kiss, Szilárd; Loewenstein, Anat; Augustin, Albert J.; Shih, Vanessa; Xu, Xiaoshu; Wykoff, Charles C.; Whitcup, Scott M. (Eye (London), 2020)
Background/objectives This post hoc analysis explores the relationship between residual oedema exposure after ranibizumab treatment initiation and long-term visual acuity outcome in eyes with centre-involved diabetic macular oedema (DMO). Subjects/methods Eyes randomised to the ranibizumab + prompt or deferred laser treatment arms in the Protocol I trial and with observed central retinal thickness (CRT) readings at baseline and ≥1 follow-up visits ( n = 367) were stratified by 1) oedema duration (number of study visits with CRT ≥ 250 µm during the first 52 weeks of ranibizumab treatment); and 2) oedema extent (amount of excess CRT [≥ 250 µm] at each study visit, averaged over the first 52 weeks). Associations between measures of residual oedema and best-corrected visual acuity (BCVA) were assessed in multiple regression analyses. Results Oedema duration and oedema extent during the first 52 weeks of ranibizumab treatment showed significant negative associations with BCVA improvement at weeks 52, 104 and 156. Eyes with the most persistent oedema gained (mean) 4.4 (95% CI 0.1─8.7) fewer Early Treatment Diabetic Retinopathy Study (ETDRS) letters at week 156 than eyes with the least persistent oedema ( P